Diamond and Carbon Composites and Nanocomposites 2016
DOI: 10.5772/63549
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Nanodiamond in Biotechnology and Tissue Engineering

Abstract: Diamond in the allotrope form consists of carbon atoms arranged in a cubic crystal structure covalently bonded in sp 3 hybridization. Diamond has emerged as a very promising material for various biomedical applications due to its excellent mechanical properties (hardness, low friction coefficient, good adhesiveness to the underlying substrate, good interlayer cohesion), optical properties (the ability to emit intrinsic luminescence), electrical properties (good insulator in the pristine state and semiconductor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 126 publications
0
19
0
Order By: Relevance
“…In order to enhance a materials’ ability to promote cell proliferation, recent biomaterial development includes addition of nanoparticles in order to obtain optimal cell-scaffold interaction [17]. NDs are known for their exquisite properties and good interaction with cells and this has been proven several times in different studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to enhance a materials’ ability to promote cell proliferation, recent biomaterial development includes addition of nanoparticles in order to obtain optimal cell-scaffold interaction [17]. NDs are known for their exquisite properties and good interaction with cells and this has been proven several times in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Guarino et al [54] showed that human mesenchymal stem cells had a superior interaction with PCL membranes when gelatin was added to their structure. Besides, NDs have also shown to enhance cell adhesion due to their favorable physical proprieties [17,18]. Pereia et al [55] fabricated a poly (lactic acid) scaffold which contained NDs and investigated biological and bioactive proprieties of this electrospun fiber.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical properties of nanodiamonds include low chemical reactivity and resistance to liquid-and gas-phase oxidations. However, nanodiamonds can be doped with various atoms, and their surface can be functionalized by various atoms, chemical groups and (bio)molecules ( [152,153,157,158]; for a review, see [10][11][12][13][14][15]155]). Scheme of a nanodiamond (a) and of the preparation and structure of nanocellulose/nanodiamond composites (b).…”
Section: Characterization Of Nanodiamondmentioning
confidence: 99%
“…Moreover, diamond represents a new class of material with properties that are tailorable on demand [ 2 ]. This work investigates the use of diamond nanomaterials, or nanodiamonds (NDs), especially in life sciences, tissue engineering and regenerative medicine [ 3 – 6 ]. Diamond is biocompatible [ 7 8 ], and for advanced biomedical applications, it is particularly promising in its nanostructured forms (nanoparticles, nanostructured diamond films and composite scaffolds) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%